Governance and performance of microfinance institutions in Mediterranean countries - Bassem, Ben Soltane (Journal of Business Economics and Management, 2009)
This paper examines empirically the relation between governance mechanisms and the performance of Euro‐Mediterranean microfinance institutions (MFIs) in terms of outreach and sustainability. Specifically, we found that performance‐based compensation of managers is not associated with better performance of MFIs. The results identify trade‐offs between MFIs outreach and sustainability depending on larger board size, and on higher proportion of unaffiliated directors. Moreover, the study shows that the more women there are on the board the better the performance, and reveals that external governance mechanisms help MFIs to achieve better financial performance. This study also allows us to distinguish other factors leading to better sustainability such as Regulation, and the use of individual lending methodology. However, the MFIs, active as NGOs, seem to be more consistent with their social mission than with their financial performance.First Publish Online: 14 Oct 2010